Screening of Diabetes in Pregnancy at Nepalgunj Medical College Teaching Hospital Kohalpur - Sharma, Nirmala; BC, Durga (Journal of Nepalgunj Medical College, 2021)
Introduction: Gestational Diabetes Mellitus (GDM) is defined as glucose intolerance of variable severity or hyperglycemia occuring for the first time during pregnancy but the glucose intolerance reverting back to normal after the puerperium. According to American Diabetic Association, approximately 7% of all pregnancy are complicated by Gestational Diabetes Mellitus, resulting in more than two lakhs cases annually and the prevalence may range from 1-14% of all pregnancies. Gestational Diabetes Mellitus usually develop in the second trimester and carries grave prognosis both for mother and fetus. So screening of diabetes is necessary for early detection of diabetes and prevention of further progression.Aims: Screening of impaired glucose tolerance and gestational  diabetes mellitus by glucose challenge test (GCT) and oral glucose tolerance test (OGTT) at 24-28 weeks of pregnancy.Methods: This study  was conducted in Nepalgunj Medical College Teaching Hospital over one year period taking 98 pregnant women who came to ANC (Antenatal Check up) out patient department. Screening for diabetes was done giving 50 gm of oral glucose (glucose challenge test) to the pregnant women at 24-28 weeks of gestational age.Results: The incidence of Impaired glucose tolerance  and gestational diabetes in this study population was  4.1% and 1% respectively.Conclusion: Screening of Diabetes mellitus in Second trimester of pregnancy is important investigation to be done to prevent the mother and the fetus from many upcoming complications of diabetes.